Galvanizing political commitment in the UN Decade of Action for Nutrition: Assessing commitment in member-countries of the Scaling Up Nutrition (SUN) Movement. (January 2020) - Fracassi, Patrizia; Siekmans, Kendra; Baker, Phillip
Highlights: This study aims to measure political commitment for nutrition in SUN countries. Early SUN joiners have higher expressed, institutional and operational commitment. There is a strong, positive relationship between institutional and operational commitment. High operational and embedded commitment associates with lower child stunting and women's anaemia. System-wide political commitment is important for achieving nutrition impact. Abstract: In pursuit of the global ambition of ending all forms of malnutrition, it is important to understand, measure and strengthen political commitment for nutrition. Building commitment involves advocating, establishing institutions, adopting policies, mobilizing resources and coordinating responses – within and outside of government, across sectors, from national to local levels – for as long as necessary to ensure results, sustained over time. As the Scaling Up Nutrition (SUN) Movement enters its tenth year of existence, this study asks if political commitment for nutrition is evident in the 60 SUN member countries and how this commitment translates into results. Guided by a theoretical framework, we use indicators from the SUN Movement's Monitoring, Evaluation, Accountability and Learning (MEAL) system to measure five forms of political commitment for nutrition - expressed, institutional, operational, embedded and system-wide - in countries stratified by income and duration of SUN membership. We further determine the association between assessed levels of commitment and progress towards achieving established global nutrition targets. In doing so, we identity important commitment gaps. Results show that countries that joined the SUN Movement early (2010–12) had higher expressed and institutional commitment scores compared with late joiners (2013–17), with no difference between low and middle-income countries. For operational commitment, early joiners had higher scores for the finance and legislation subcomponents but not for nutrition-specific intervention coverage. Low-income countries, however, had significantly lower scores for the nutrition-specific intervention coverage sub-component of operational commitment and lower embedded commitment scores compared with middle-income countries. A positive association was found between institutional and operational commitment, irrespective of country economic status. Early joiners in the SUN Movement were more likely to rank in the top half of SUN countries for all four forms of commitment. When divided into terciles based on their overall rank for system-wide political commitment, countries in the highest tercile were more likely to be making progress in the reduction of U5 child stunting. The results point to the importance of working to strengthen all forms of commitment, especially converting expressed and institutional commitments into operational commitment. While institutional commitment matters, it can be 'tokenistic' only if there is limited capacity to operationalise that commitment. Countries with system-wide political commitment appear to achieve better nutrition impact. It is difficult to determine whether early joiners were already more committed to nutrition and therefore more likely to join the SUN Movement or whether membership in the SUN Movement compelled such commitment. Most likely it is a combination of both, but it is hard to disentangle the direction of causality without measuring changes in commitments over time, and complementing this type of analysis with qualitative research on the perspectives of different stakeholders. Nonetheless, the ongoing measurement and reporting of political commitment can inform dialogue with country and global-level stakeholders on how to galvanize further commitment during the UN Decade of Action on Nutrition especially in view of the 2020 Nutrition for Growth (N4G) Summit in Tokyo, Japan.